EFFECTS OF ENTREPRENEURIAL UNIVERSITIES ON ECONOMIC, SOCIAL AND CULTURAL SUSTAINABILITY - Yilmaz, Tamer; Keskin, Halit; Aksoy, Zeynep (TUBA-TURKISH ACAD SCIENCES, 2022)
Developments in industry and increased world population cause risk of the depletion of scarce and vital resources and initiate discussions on how to ensure a sustainable future. It thus puts a pressure on both individuals and organizations to carry out activities that contribute to sustainability. At this point, the third mission of universities, serving the society, has come into prominence and universities are expected to support sustainable development by adopting an entrepreneurial business model. Although previous studies examined the effects of entrepreneurial universities that transform technological knowledge into a commercial product on economic sustainability, this study provides a more comprehensive perspective for the entrepreneurial university concept and its impacts. In this regard, this study examines the effects of entrepreneurial universities that perform economic, social, and cultural entrepreneurship activities on different dimensions of sustainability and illuminates the role of entrepreneurial universities in the process of creating a sustainable future.
Keywords: Sustainability; entrepreneurial university; entrepreneurship; economic growth; social impact; 3RD MISSION; INNOVATION; IMPACT; HELIX; Business & Economics; Science & Technology - Other Topics